Clinical features, diagnostic challenges, and management strategies in checkpoint inhibitor-related pneumonitis - Chuzi, Sarah (2018)
Abstract: Immune checkpoint inhibitors, including cytotoxic T-lymphocyte antigen 4 (CTLA-4) and programmed cell death-1 (PD-1) inhibitors, represent an effective treatment modality for multiple malignancies. Despite the exciting clinical benefits, checkpoint inhibition is associated with a series of immune-related adverse events (irAEs), many of which can be life-threatening and result in significant treatment delays. Pneumonitis is an adverse event of special interest as it led to treatment-related deaths in early clinical trials. This review summarizes the incidence of pneumonitis during treatment with the different checkpoint inhibitors and discusses the prognostic significance of tumor type. The wide range of clinical, radiographic, and histologic characteristics of checkpoint inhibitor-related pneumonitis is reviewed and followed by guidance on the different management strategies.